Travel survey of residents of Canada, travel characteristics, by province visited, 2011 - 2012 - Statistics Canada (Government of Canada, 2018)
This table contains 803 series, with data for years 2011 - 2012 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography, province visited (11 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...), Visits characteristics (38 items: Visit duration, total, same day and overnight; Visit duration, same day; Visit duration, overnight; Visits first quarter; ...), Type of visit duration (2 items: Total visits; Overnight visits).